Association of Demographics and Hospital Stay Characteristics With Patient Experience in Hospitalized Pediatric Patients - Jerome Gene Chen MD, MHS; Stacey Lee MS; Bertha Ben Khallouq MA (Journal of Patient Experience, 2020)
There is limited research on patient experience in hospitalized pediatric patients. Our aim was to investigate the association of patient demographics and hospital stay characteristics with experience in a tertiary-care, freestanding children’s hospital. We conducted a retrospective cross-sectional study of patient experience surveys. We designated the highest rating as “top-box” and examined data across 8 domains, including overall assessment (OA). A total of 4602 surveys were analyzed. Top-box percentages were lower for younger patients in 6 domains, including OA (0-<1 year old: 57.6%; 1-<4 years old: 61.3%; 4-<12 years old: 68.4%; ≥12 years old: 70.2%; P < .001), and were lower for patients with private insurance in 5 domains, including OA (private 63.2%, public 68.9%; P < .001). There was no association between other demographics (gender, race/ethnicity, primary language) and OA. Overall assessment was also not associated with length of stay ( P = .071) and number of consulting services ( P = .703). The most important domain predictor of OA was personal issues (odds ratio = 4.79), which assessed concern, sensitivity, and communication from staff. In conclusion, patient experience was associated with age and insurance status but not hospital stay characteristics.